1993
DOI: 10.1159/000243969
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Copper and Zinc during Rat Development

Abstract: The association of copper and zinc to plasma ligands was studied during the rat perinatal period. Analysis was carried out by means of column chromatography (Sephadex G-150) and atomic absorption spectrophotometry. Levels of copper were low at birth and showed a sharp increase after day 10. This increase was similar to that of ceruloplasmin activity as well as its association with copper. Zinc levels, instead, showed higher levels before birth and decreased slowly toward the adult values. Association of zinc t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In contrast to Cu, Zn levels in plasma are reported to steadily decrease with age from birth (Bunker et al 1987;McMaster et al 1992;Martinez Lista et al 1993;Madaric et al 1994) and the presence of Zn ions in serum and blood is further decreased in AD compared with age-matched control patients (Basun et al 1991;Baum et al 2010;Brewer et al 2010). Conversely, the level of Zn in CSF has been reported to be elevated, reflecting the rise observed within the brain (Deibel et al 1996;Cornett et al 1998;Religa et al 2006).…”
Section: Zinc Levelsmentioning
confidence: 99%
“…In contrast to Cu, Zn levels in plasma are reported to steadily decrease with age from birth (Bunker et al 1987;McMaster et al 1992;Martinez Lista et al 1993;Madaric et al 1994) and the presence of Zn ions in serum and blood is further decreased in AD compared with age-matched control patients (Basun et al 1991;Baum et al 2010;Brewer et al 2010). Conversely, the level of Zn in CSF has been reported to be elevated, reflecting the rise observed within the brain (Deibel et al 1996;Cornett et al 1998;Religa et al 2006).…”
Section: Zinc Levelsmentioning
confidence: 99%
“…Normally, the levels of plasma Cu in rats are low at birth but sharply increase after day 10, whereas Zn plasma levels are high before birth and decrease slowly toward the adult value [12]. In contrast, Cu and Zn in the breast milk of humans continuously decrease [13].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, plasma Zn levels were highest at birth and decreased slowly to adult values [26]. Older rats (20-22 months) have also been shown to have lower total plasma Fe content than middle aged rats (8-10 months), in addition to lower levels of the Fe-containing protein, hemoglobin [27].…”
Section: Aging and Metalsmentioning
confidence: 98%
“…CQ doses were 125 mg twice daily (first 12 weeks), 250 mg twice daily (weeks [13][14][15][16][17][18][19][20][21][22][23][24] and 375 mg twice daily (weeks [25][26][27][28][29][30][31][32][33][34][35][36]. Subsequent analysis of patients revealed that CQ significantly arrested the rate of cognitive decline (on ADAS-cog) at week 24 (and a tendency to significance at week 36) in the patients suffering moderate dementia [180].…”
Section: Treatment Of Alzheimer's Disease Patients With Cqmentioning
confidence: 99%